Robust Red Organic Nanoparticles for In Vivo Fluorescence Imaging of Cancer Cell Progression in Xenografted Zebrafish. (3rd July 2017) - Lin, Gengwei; Manghnani, Purnima Naresh; Mao, Duo; Teh, Cathleen; Li, Yinghao; Zhao, Zujin; Liu, Bin; Tang, Ben Zhong
Abstract : Bright and red‐emissive organic nanoparticles (NPs) are demonstrated as promising for in vivo fluorescence imaging. However, most red organic dyes show greatly weakened or quenched emission in the aggregated state. In this work, a robust red fluorophore ( t ‐BPITBT‐TPE) with strong aggregate‐state photoluminescence and good biocompatibility is presented. The NPs comprised of t ‐BPITBT‐TPE aggregates encapsulated within 1, 2‐distearoyl‐ sn ‐glycero‐3‐phosphoethanolamine‐ N ‐[methoxy(polyethylene glycol) (DSPE‐mPEG) micelles exhibit a photoluminescence peak at 660 nm with a high fluorescence quantum yield of 32% in aqueous media. The NPs can be facilely charged by using the same polymeric matrix with different terminal groups, e.g., methoxy (DSPE‐mPEG), amine (DSPE‐PEG‐NH2 ), or carboxymethyl (DSPE‐PEG‐COOH) groups. The biocompatibility, toxicity, circulation, and biodistribution of the NPs are assessed using the zebrafish model through whole embryo soaking and intravenous delivery. Furthermore, HeLa and MCF‐7 cells tagged with t ‐BPITBT‐TPE in DSPE‐PEG‐NH2 ‐TAT polymer NPs are xenografted into zebrafish larvae to successfully track the cancer cell proliferation and metastasis, demonstrating that these new NPs are efficient cancer cell trackers. In addition, the NPs also show good in vivo imaging ability toward 4T1 tumors in xenografted BALB/c mice. Abstract : Bright red organic nanoparticles are prepared for the study of their toxicity, circulation, and biodistribution in zebrafish. Different cancer cells tagged with these nanoparticles are xenografted into zebrafish larvae, realizing long‐term tracing of their proliferation and metastasis in zebrafish.